Penerapan metode direct costing sebagai metode untuk menghitung harga pokok produksi pada JM Bakery Manado - Salmawati, Fitri; Alexander, Stanly W.; Lintong, Diana N. (Yayasan Widyantara Nawasena Raharja, 2025)
JM Bakery Manado is a bread production business. It produces every day except Sunday, but its cost of production calculation is outdated and inaccurate. It uses a traditional method that fails to group costs based on cost elements, and it does not distinguish between direct and indirect costs. This study aims to implement the direct costing method to improve the accuracy of JM Bakery Manado's cost calculations. This study used a qualitative descriptive method with primary data, collected through observation and interviews. The results are clear: the cost of production calculated by JM Bakery Manado is higher than the direct costing calculation (IDR 37,832,500), while the direct costing calculation is lower (IDR 36,120,833.3). The difference between the two methods is IDR 1,711,666.7. This is because the company calculates all costs incurred during the production process, both direct costs and indirect costs, and does not include machine depreciation costs and auxiliary material costs. JM Bakery Manado should therefore apply the direct costing method, as this only considers costs that are directly related to the product.